Interface Oral Health Science 2014 2015
DOI: 10.1007/978-4-431-55192-8_29
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Aspiration Pneumonia Among the Elderly: A Review Focused on the Impact of the Consistency of Food Substances

Abstract: Aspiration pneumonia is the leading cause of death among the elderly. Modified-texture foods, i.e., foods with altered consistency, are recommended in order to maintain both normal swallowing and adequate nutrition, which is also expected to reduce aspiration pneumonia, when elderly people are suspected to suffer from disorders of eating and/or swallowing. However, it is reported that overly-restrictive diets have been provided to most residents given modified-texture diets. Furthermore, there is scant empiric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 101 publications
1
1
0
Order By: Relevance
“…Tube feeding is associated with a higher risk of aspiration pneumonia compared to oral feeding (32,49), and our study showed similar results (adjusted HR 2.57, 95% CI: 1.61-4.12, P < 0.001) under multivariate analysis. Although PEG has not shown more favorable outcomes compared to NGT in meta-analyses (15,22), subgroup analysis in this study demonstrates that the risk of pneumonia was significantly reduced in PEG compared to NGT in older patients with oropharyngeal dysphagia (adjusted HR 0.26, 95% CI: 0.11-0.63, P = 0.003), but not in patients without oropharyngeal dysphagia (adjusted HR 1.57, 95% CI: 0.71-3.45, P = 0.261).…”
Section: Older Patients With Oropharyngeal Dysphagiasupporting
confidence: 80%
“…Tube feeding is associated with a higher risk of aspiration pneumonia compared to oral feeding (32,49), and our study showed similar results (adjusted HR 2.57, 95% CI: 1.61-4.12, P < 0.001) under multivariate analysis. Although PEG has not shown more favorable outcomes compared to NGT in meta-analyses (15,22), subgroup analysis in this study demonstrates that the risk of pneumonia was significantly reduced in PEG compared to NGT in older patients with oropharyngeal dysphagia (adjusted HR 0.26, 95% CI: 0.11-0.63, P = 0.003), but not in patients without oropharyngeal dysphagia (adjusted HR 1.57, 95% CI: 0.71-3.45, P = 0.261).…”
Section: Older Patients With Oropharyngeal Dysphagiasupporting
confidence: 80%
“… Although the risk of aspiration in instrumental studies is reduced with liquids with increasing degrees of thickness, higher viscosity liquids also result in increased pharyngeal residue after swallowing with the potential for increased aspiration risk [ 28 ]. The same may be true for some modified texture foods [ 25 ]. …”
Section: Discussionmentioning
confidence: 91%